Advances in Thermoelectric Materials—Bridging the Gap Between Discovery and Application - Marco Fronzi; Paolo Mele; Giovanna Latronico (Inorganics)
Thermoelectric materials have gained considerable attention in recent years due to their ability to directly convert heat into electricity, making them a key focus in the development of sustainable energy technologies [...]